Законодавче забезпечення процесу підготовки науково-педагогічних кадрів в університетах України (друга половина ХІХ – початок ХХ століття) - Таможська, Ірина Володимирівна; Tamozhska, Iryna Volodymyrivna (Запоріжжя : Класичний приватний університет, 2020)
Викладено проблему підготовки науково-педагогічних кадрів в університетах України другої поло вини ХІХ – початку ХХ століття. Визначено нормативно-правову базу, яка регламентувала підготовку науково-педагогічних кадрів в університетах України досліджуваного періоду, що мала характер підзаконних актів (розпорядження, постанови, циркуляри, інструкції, правила). Встановлено, що однією з дієвих форм підготовки науково-педагогічних кадрів став інститут «професорських стипендіатів». З’ясовано обов’язки «професорських стипендіатів», пов’язані з навчальною, науково-дослідною та викладацькою діяльністю. Акцентовано увагу на зміні вимог до звітів, що подавалися до Міністерства народної освіти, про проведення занять «професорськими стипендіатами».
Legislative provision for the process of academic staff training in Ukrainian universities (the second half of XIX – at the beginning of XX century)
The article deals with the problem of the academic staff training in the universities of Ukraine in the second half of XIX – at the beginning of XX century. The regulatory and legal framework, which regulated the training of academic staff in Ukrainian universities during the researched period, is determined. It mostly included by-laws (decrees, resolutions, circulars, instructions, rules). It is established that the institute of “professor scholarship holders” became one of the effective forms to train academic staff. The responsibilities of “professor scholarship holders” are singled out. They were connected with their learning, scientific and research, teaching activities. Particular attention is drawn to changing the requirements for the reports submitted to the Ministry of Public Education, which dealt with holding classes by “professor scholarship holders”.
Keywords: HUMANITIES and RELIGION; законодавче забезпечення; науково-педагогічні кадри; розпорядження; постанови; циркуляри; інструкції; правила; «професорські стипендіати»; закордонні відрядження «з науковою метою»; звіт; legislative provision; academic staff; decrees; resolutions; circulars; instructions; rules; “professor scholarship holders”; foreign trips “for scientific purposes”; report